Modeling and observational study of the daytime evolution east of the crest of the Colorado Rockies - Wolyn, Paul George, author; McKee, Thomas B., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1992)
The west-east nature of the daytime evolution east of the Front Range of the Colorado Rockies in the vicinity of Fort Collins, Colorado is examined for conditions of clear skies, little change to the synoptic-scale wind and thermal fields, and light ambient winds with a westerly component (around 5ms-1). The observations mainly consist of airsondes launched at every 2-3 hours at sites on the eastern plains and on the east slope of the mountain barrier. A variety of two-dimensional simulations using the CSU RAMS are run with varying initial conditions that change the surface heating, ambient winds, ambient thermal structure, and barrier height. A full nighttime phase is simulated before the daytime phase. From the observations and simulations a conceptual model of the daytime is developed. The sunrise state includes a strong jet down the east side of the barrier and a deep layer of stability to the east of the barrier. Phase 1 of the evolution lasts until 3-4 hours after sunrise and results from the weakening nocturnal flow interacting with the early daytime heating. Phase 2 has a solenoid which is not symmetric horizontally and which does not develop uniformly with time. Phase 3 is characterized by a solenoid which migrates eastward. The variety of simulations show how the daytime evolution changes for the various initial conditions. Generally, the solenoid in phases 2 and 3 is weaker and shallower for moister soil (less surface sensible heat flux) on the plains east of the barrier, moister soil west of barrier crest, days closer to the winter solstice, stronger ambient winds, and a lower convective boundary layer (CBL) the previous day. The solenoid is generally deeper and stronger for less ambient stability and days closer to the summer solstice. The usefulness of vertical integrals of heating and mass flux in the analysis of simulations and observations is explored in this study. These vertical integrals quantify the movement of energy and mass at different heights by the circulations, and they are very useful for comparing the strength and depth of the circulations among simulations and between the simulations and observations.
April 1992.
Keywords: Atmospheric circulation -- Colorado; Meteorology -- Diurnal variations